Quasi-Continuous Tidal Datum for Peninsular Malaysia using Tide Gauge, Satellite Altimetry, and Tide Model Driver (TMD) Data - Abd Rahman, Mohd Faizuddin; Din, Ami Hassan Md; Mahmud, Mohd Razali; Hamden, Mohammad Hanif (Engineering, Technology & Applied Science Research, 2024)
Conventionally, information from the tide gauge stations was used to establish the localized tidal datum. However, limitations in coverage, due to the sparse station distribution along the coast, have caused insufficient tidal datum information in some areas. Therefore, this study aims to develop the Peninsular Malaysia Quasi-Continuous Tidal Datum (PMQCTD) by integrating tide gauges, satellite altimetry, and Tide Model Driver (TMD) data. The research methodology includes data acquisition from 12 Departments of Survey and Mapping Malaysia (DSMMs) tide gauge stations along the coast of Peninsular Malaysia, satellite altimetry data of TOPEX, Jason-1, Jason-2, and GEOSAT Follow-On (GFO) from Radar Altimeter Database System (RADS), and the global hydrodynamic model from TMD. The tide gauge, satellite altimetry, and TMD data encompass 23 years of tidal observation data from 1993 to 2015. For the derivation of the tidal datum, tide gauge, and satellite altimetry data were analyzed following a harmonic analysis approach in the Unified Tidal Analysis and Prediction (UTide) software. Meanwhile, for the TMD data, the tidal datum was determined based on the tidal prediction from the 11 extracted major tidal constituents. For compatibility in data integration, the derived Lowest and Highest Astronomical Tide (LAT and HAT) from tide gauge, satellite altimetry, and TMD data were referenced to the Mean Sea Level (MSL), denoted as LATMSL and HATMSL, respectively. Next, the LATMSL and HATMSL were interpolated employing Inverse Distance Weighting (IDW) to develop the PMQCTD (LATMSL and HATMSL) with the ArcGIS software. The statistical assessment indicated that the established PMQCTD (LATMSL and HATMSL) has a better agreement with the DSMM tide gauges with a Root Mean Square Error (RMSE) of ± 0.228 m for LATMSL and ± 0.159 m for HATMSL In conclusion, the establishment of PMQCTD (LATMSL and HATMSL) has led to the availability of the tidal datum at any location along the coast of Peninsular Malaysia.